The Effectiveness of Cognitive Behavioral Therapy on Symptoms of Depression among Syrian Children Refugees in Kurdistan Region of Iraq - Jassim, Arazo Adil; Gardi, Abdulqader Hussein (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Cognitive behavioral therapy is helpful verbal therapy to reduce symptoms of depression in children. It always includes parent involvement, teaching skills that are practiced at home or school, and measures of progress that are tracked over time. Objective: This study aimed to assess the effectiveness of the psychoeducational program for reducing symptoms of depression in Syrian children. Methods: We used a quasi-experimental research design to survey 272 children living in Arbat Campus Refugee, Kurdistan Region-Iraq, from Nov. 5, 2020, until Nov. 20, 2021 (data collection and program intervention). Sociodemographic data were collected from the participants/parents using a specific questionnaire, and CBT was applied to the experimental group. Results: A non-probability, purposive sample size of 272 children were divided into experimental and control groups with 136 children each aged 5-13 years, using the simple random sampling approach. The socio-demographic data revealed that most children were 11-13 years, and most were females, and also appears that most of the families have 4-6 children. Additionally, most of the parents have a basic level of education with psychological distress among their parents very highly. Additionally, highly frequent behavioral characteristics were found in the sample response table 2 (88.2%). Conclusion: We concluded that the Cognitive behavioral therapy intervention is effective in reducing symptoms of depression among Syrian refugee children living on the Arbat campus that might be due to their parent's significant psychological distress
Keywords: Cognitive behavioral therapy; Depression; Refugee children; Parent distress; Arbat campus